The Relationship Between Self-Adjustment and Emotion Regulation with Problem Solving in Overseas Students from Outside Java at UIN Malang - Ulfah, Maziah (International Journal of Educatio Elementaria and Psychologia, 2024)
The number of problems faced by students requires the ability to overcome and deal with every problem that comes their way. Every student needs to have the right problem solving skills so that problems can be solved properly. Therefore in this study will examine what factors are positively correlated with problem solving. So this study aims to determine the correlation between self-adjustment variables and emotional regulation together with problem solving variables in overseas students who come from outside the island of Java who study at UIN Malang as many as 50 people. The method used is a quantitative research method using a Likert scale. As for the analysis of the results used is correlation analysis. Based on the results of data processing, this study provides several conclusions, namely the variables of self-adjustment and emotional regulation correlate with problem solving by 66.5% and the remaining 33.5% are influenced by other variables and factors. The correlation between problem solving variables and self-adjustment is 0.59 and is positive so that the two variables are stated to have a positive correlation. Furthermore, the correlation between self-adjustment variables and emotional regulation is 0.46, which means that the two variables are positively correlated. From the results of this analysis it can be seen that problem solving has a high relationship with emotional regulation variables than problem solving with self-adjustment in overseas students who come from outside Java.